Adsorption enhanced conversion of oxygenates to hydrocarbons

By introducing adsorbent materials that can adsorb water in the presence of catalysts, the conversion rate and reaction rate of oxygenated compounds into hydrocarbons are improved, the problems of catalyst deactivation and low high-temperature reaction efficiency are solved, and lower energy consumption and higher efficiency are achieved craftsmanship.

CN119365566APending Publication Date: 2025-01-24NEDERLANDSE ORG VOOR TOEGEPAST NATUURWETENSCHAPPELIJK ONDERZOEK TNO
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380046614.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-30
Filing Date
2023-05-26
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Prior art In the process of converting oxygen-containing compounds into hydrocarbons, rapid coking of the catalyst leads to inactivation, and low reaction efficiency at high temperatures, and there is a need for catalyst decoking.

Method used

The introduction of adsorbent materials that can adsorb water can increase the conversion rate of oxidant compounds to hydrocarbons by co -existence with catalysts, and reduce the loss of catalyst through the regeneration steps of adsorbents.

Benefits of technology

The conversion rate and response rate have been improved, the reaction temperature is reduced, the life of the catalyst is prolonged, and the demand for removing the catalyst removal is reduced, and the overall process efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005184221820000171
    Figure BDA0005184221820000171
  • Figure BDA0005184221820000181
    Figure BDA0005184221820000181
  • Figure HDA0005184221830000011
    Figure HDA0005184221830000011
Patent Text Reader

Abstract

The present invention relates to a process for converting oxygenates to hydrocarbons in the presence of a sorbent material capable of adsorbing water. Furthermore, the invention relates to a fluidized bed or fixed bed reactor for converting oxygenates into hydrocarbons, the reactor comprising a catalyst and an adsorbent material capable of adsorbing water. The invention also relates to the use of an adsorbent material capable of adsorbing water for increasing the conversion of oxygenates to hydrocarbons.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] There is an increasing interest in renewable resources for the production of the following chemical building blocks: hydrocarbons such as olefins, alkanes and aromatic compounds. By choosing renewable resources instead of oil and natural gas, the environmental impact of these chemical building blocks is significantly reduced. Oxygenated compounds such as methanol and dimethyl ether (DME) are typical intermediates obtained in carbon capture and utilization processes or in the bioconversion of organic waste streams. These oxygenated compounds can subsequently be converted into hydrocarbons of interest.

[0002] The conversion of oxygenates into hydrocarbons is known in the art. Water is separated from the oxygenates and hydrocarbons are formed without ether and / or alcohol groups. The reaction is exothermic. The specific mixture of hydrocarbons formed depends on the reaction conditions such as pressure and temperature and the selected catalyst (Gunawardena et al., Journal of Thermodynamics, Vol. 2012, pp. 1-7). A large amount of literature is available on the selection of reaction conditions and catalysts. The hydrocarbons formed are olefins, alkanes and / or aromatic compounds. These methods are typically carried out at high temperatures to obtain sufficiently high conversions. The corresponding rapid coking of the catalyst (which typically occurs within 50-100 minutes) is alleviated by incorporating a continuous decoking step into the method. The optimum temperature depends on the catalyst provided, the target hydrocarbon and the oxygenate. Typically, methanol reacts at a temperature of about 450° C., while, for example, dimethyl ether reacts at about 350° C.

[0003] An overview of methanol to aromatics (MTA) is provided by Li et al. (ACS Catal. 2021, 11, 7780-7819), an overview of methanol to olefins (MTO) is provided by Tian et al. (ACS Catal. 2015, 5, 1922-1938) and also by Topchiev et al. (Catalysts 2019, 9(5), 485), and the prior art of methanol to alkanes (MTG) is provided by Sanz-Martinez et al. (Catalysts 2022, 12, 134). Magomedova et al. (Catalysts, 2019, 9, 485) describe the conversion of dimethyl ether to olefins.

[0004] In WO 9955650 A1, the conversion of methanol to olefins (MTO) in the presence of a catalyst is disclosed. In order to alleviate the rapid coking of the catalyst, the catalyst is regenerated using an oxygen-containing gas at high temperature. Water is removed from the product stream by a quenching step, in which the quenching medium is water. US2019001311 describes an MTO method using an acidic zeolite catalyst comprising ZSM-5 and bentonite clay. Bentonite clay bonds ZSM-5 particles to make the catalyst structure complete. In US2015119617A1, water is removed from the product stream. The removal of water is completed by a quenching step of the olefin stream, after which the stream is contacted with a molecular sieve comprising zeolite 3A and / or 4A to remove water from the quenched olefin stream. The regeneration of the catalyst is carried out using an oxygen-containing gas / oxidant at a temperature between 200°C and 1500°C. WO 2006 / 104757 describes a method for reducing catalyst deactivation. A coked catalyst is regenerated using a regeneration gas, wherein the regeneration temperature is not greater than 600° C. Before regenerating the coked catalyst, the regeneration gas may be compressed to condense a portion of the water and may be contacted with a water adsorbent. Summary of the invention

[0005] The inventors unexpectedly found that the conversion rate of the method of oxygen-containing compounds to hydrocarbons can be increased by introducing an adsorbent material capable of adsorbing water. In Example 1, unexpectedly, the conversion rate of DME in the presence of an adsorbent material capable of adsorbing water is much higher than the conversion rate when the adsorbent material is saturated with water so that the effect of the adsorbent material is offset. The inventors found that not only the conversion rate to hydrocarbons is improved, but also that the absolute concentration of the reactants will be higher, thereby increasing the reaction rate. Therefore, through this adsorption-based enhancement, a lower reaction temperature can be selected, which is more energy-efficient and requires less capital investment for heating equipment and heat-resistant materials. In addition, the operating window of the process design for the method of converting oxygen-containing compounds to hydrocarbons is expanded; this can open up possibilities for new reaction product mixtures. The reaction window is extended to lower temperatures and possibly higher pressures.

[0006] Furthermore, the inventors unexpectedly discovered that catalyst deactivation due to coking is reduced or even avoided. In Example 3, the reactor was operated in a cycle, with the steps of oxygenate reaction and adsorbent material regeneration being performed continuously. After 50 cycles, no catalyst degradation was observed. Without being bound by theory, the inventors believe that lower reaction temperatures and changes in gas composition contribute to this unexpected improvement. Since catalyst deactivation is reduced or even avoided, less or no catalyst decoking is required, thereby improving overall process efficiency. A specific catalyst decoking step may not be required or less required.

[0007] In a preferred embodiment, the method comprises two or more reactors comprising a catalyst and an adsorbent material capable of absorbing water. Such a combination of reactors can be operated in a pressure fluctuation, temperature fluctuation and / or concentration fluctuation mode, wherein at least one of the reactors is in a reaction mode. At the same time, one or more of the other reactors are in an adsorbent regeneration mode. In this way, the entire process can be carried out continuously. Such operation has the additional advantage that one of the reactors can be in a decoking mode while some catalyst coking still occurs. A separate decoking reactor is not required, and there is greater flexibility in reactor design, since transporting the catalyst to a specific decoking reactor typically limits the design. During decoking, the adsorbent is typically also regenerated. DETAILED DESCRIPTION

[0008] The present invention relates in a first aspect to a method for converting oxygenates into hydrocarbons, the method comprising: a) contacting a catalyst with an oxygenate in the presence of an adsorbent material capable of adsorbing water to form hydrocarbons in a reactor; and subsequently b) regenerating the adsorbent material in the same reactor by contacting the adsorbent material with a purge gas; The catalyst and adsorbent materials are different.

[0009] Furthermore, the present invention relates to a fluidized bed or fixed bed reactor for converting oxygenates into hydrocarbons, the reactor comprising a catalyst for converting oxygenates into hydrocarbons and an adsorbent material capable of adsorbing water, wherein the catalyst and the adsorbent material are different.

[0010] The present invention also relates to the use of an adsorbent material capable of adsorbing water for converting oxygenates into hydrocarbons in the presence of a catalyst for converting oxygenates into hydrocarbons, wherein the catalyst and the adsorbent material are different, preferably wherein the use involves one or more of the following: - Increased conversion compared to the absence of adsorbent material, - the lifetime of the catalyst is extended compared to when no adsorbent material is present, - reduced deactivation of the catalyst compared to when no adsorbent material is present, - an increase in the reaction rate compared to when no adsorbent material is present, and - The need for catalyst decoking is reduced, preferably avoided, compared to when no adsorbent material is present.

[0011] The embodiments disclosed in this document are applicable to all aspects of the invention, namely the process for converting oxygenates into hydrocarbons, the fluidized bed or fixed bed reactor for converting oxygenates into hydrocarbons and the use of an adsorbent material capable of adsorbing water for converting oxygenates into hydrocarbons in the presence of a catalyst. Conversion rate

[0012] The present invention relates to the conversion of oxygenates to hydrocarbons. Herein, one or more oxygenates undergo a chemical reaction to form one or more hydrocarbon compounds, such chemical reactions being known in the art and typically requiring a catalyst to occur. Based on common sense, a skilled person can select a combination of oxygenates, catalysts, and reaction conditions (such as pressure and temperature) to direct the reaction toward a desired mixture of specific hydrocarbons. In a preferred embodiment, at least 50 mol %, more preferably at least 70 mol %, and most preferably at least 90 mol % are hydrocarbons, based on the total moles of the reaction products excluding water.

[0013] Preferably, for the conversion of oxygenates to hydrocarbons, the conversion is at least 80%, more preferably at least 90%, even more preferably at least 95%, and most preferably at least 98%. The conversion can be calculated as follows: [(moles of oxygenates in the feed - moles of oxygenates at the end of the reaction) / (moles of oxygenates in the feed)]; expressed as %. Preferably, the reaction product of the conversion of oxygenates to hydrocarbons contains less than 20 mole %, more preferably less than 10 mole %, and most preferably less than 5 mole % of oxygenates based on the total moles of oxygenates in the feed.

[0014] In a preferred embodiment, at least 50 mol%, more preferably at least 70 mol%, most preferably at least 90 mol%, based on the total moles of the reaction product excluding water, are olefins. More preferably, at least 50 mol%, more preferably at least 70 mol%, most preferably at least 90 mol%, based on the total moles of the reaction product excluding water, are a mixture (sum) of ethylene, propylene, 1-butene, 2-butene and isobutylene. Even more preferably, at least 50 mol%, more preferably at least 70 mol%, most preferably at least 90 mol%, based on the total moles of the reaction product excluding water, are a mixture of ethylene and propylene. For this embodiment, preferably, the oxygenate is methanol or dimethyl ether.

[0015] In another preferred embodiment, at least 50 mol%, more preferably at least 70 mol%, most preferably at least 90 mol%, based on the total moles of the reaction product excluding water, are alkanes. More preferably, at least 50 mol%, more preferably at least 70 mol%, most preferably at least 90 mol%, based on the total moles of the reaction product excluding water, are mixtures of alkanes containing 2 to 18 carbon atoms. Even more preferably, at least 50 mol%, more preferably at least 70 mol%, most preferably at least 90 mol%, based on the total moles of the reaction product excluding water, are mixtures of ethane, propane, butane, isobutane, pentane, isopentane and neopentane. For this embodiment, preferably, the oxygenate is methanol or dimethyl ether.

[0016] In yet another preferred embodiment, at least 50 mol%, more preferably at least 70 mol%, and most preferably at least 90 mol%, based on the total moles of the reaction products excluding water, are aromatic compounds. More preferably, at least 50 mol%, more preferably at least 70 mol%, and most preferably at least 90 mol%, based on the total moles of the reaction products excluding water, are a mixture of benzene, toluene, and xylene. For this embodiment, preferably, the oxygenate is methanol or dimethyl ether.

[0017] For all of these examples, the total moles of reaction products excluding water refers to the total moles of reaction products minus the amount of water (expressed in moles) in the reaction products. Oxygenated compounds

[0018] Oxygenates are molecules consisting of carbon (C), hydrogen (H) and oxygen (O) atoms. For the present invention, oxygenates are typically ethers or alcohols comprising 1-6 carbon atoms. Preferably, oxygenates are composed of hydrogen, carbon and oxygen atoms. Preferably, oxygenates do not comprise double bonds. In a preferred embodiment of the present invention, oxygenates are one or more of: methanol (MeOH), ethanol (EtOH), isopropyl alcohol (IPA), n-butyl alcohol (BuOH), gasoline grade tertiary butyl alcohol (GTBA), methyl tertiary butyl ether (MTBE), tert-amyl methyl ether (TAME), tert-hexyl methyl ether (THEME), ethyl tertiary butyl ether (ETBE), tert-amyl ethyl ether (TAEE), dimethyl ether (DME) or diisopropyl ether (DIPE), more preferably oxygenates are methanol and / or dimethyl ether, even more preferably oxygenates are methanol, or even more preferably oxygenates are dimethyl ether. hydrocarbon

[0019] Hydrocarbons are molecules consisting of carbon (C) and hydrogen (H) atoms. In a preferred embodiment of the present invention, the hydrocarbons contain up to 20 carbon atoms, more preferably 2-18 carbon atoms. In a preferred embodiment, the hydrocarbons are selected from the list consisting of olefins, alkanes and aromatic compounds, more preferably the hydrocarbons are selected from the list consisting of olefins, alkanes and aromatic compounds and these hydrocarbons contain up to 20 carbon atoms, more preferably 2-18 carbon atoms; even more preferably, the hydrocarbons are selected from the list consisting of olefins, alkanes and aromatic compounds, wherein the olefins contain 2 to 5 carbon atoms, the alkanes contain 2-18 carbon atoms and the aromatics contain 6 to 8 carbon atoms.

[0020] In a preferred embodiment, the hydrocarbon is an olefin. In a preferred embodiment, the hydrocarbon is an alkane. In a preferred embodiment, the hydrocarbon is an aromatic compound.

[0021] In a preferred embodiment, the oxygenate is methanol and / or dimethyl ether and the hydrocarbon is an olefin. In a preferred embodiment, the oxygenate is methanol and / or dimethyl ether and the hydrocarbon is an alkane. In a preferred embodiment, the oxygenate is methanol and / or dimethyl ether and the hydrocarbon is an aromatic compound. Olefins

[0022] Olefins are non-cyclic hydrocarbons with one double bond. Olefins are also referred to as alkene. In a preferred embodiment of the present invention, olefins are one or more of ethylene, propylene, 1-butene, 2-butene and isobutylene. Olefins are typical structural units of other chemicals such as polymers. Alkanes

[0023] Alkanes are non-cyclic hydrocarbons without double or triple bonds. Alkanes are also known as chain alkanes. Typically, alkanes are used as fuels. In a preferred embodiment of the present invention, the alkanes contain 2 to 18 carbon atoms, more preferably 3 to 18 carbon atoms. Depending on the application, different amounts of carbon atoms are preferred. For synthetic LPG, preferably the alkanes contain 3 to 4 carbon atoms, for naphtha, preferably the alkanes contain 5 to 7 carbon atoms, for gasoline, preferably the alkanes contain 4 to 12 carbon atoms, for kerosene, preferably the alkanes contain 11 to 15 carbon atoms, and for diesel, preferably the alkanes contain 14 to 18 carbon atoms. Aromatic compounds

[0024] Aromatic compounds are hydrocarbon compounds containing aromatic rings. In a preferred embodiment, the aromatic compound contains a benzene ring. In a preferred embodiment of the present invention, the aromatic compound is one or more of benzene, toluene and xylene. catalyst

[0025] A large number of documents on catalysts for converting oxygenates to hydrocarbons have been disclosed. For example, Li et al. (ACS Catal. [ACS Catalysis Magazine] 2021, 11, 7780-7819) provide an overview of catalysts for conversion to aromatic compounds (MTA), Tian et al. (ACS Catal. [ACS Catalysis Magazine] 2015, 5, 1922-1938) and also Topchiev et al. (Catalysts [Catalyst] 2019, 9 (5), 485) provide an overview of catalysts for conversion to olefins (MTO), and Sanz-Martinez et al. (Catalysts [Catalyst] 2022, 12, 134) provide prior art on catalysts for conversion to alkanes (MTG). Typically, a catalyst containing acid sites is tailored to its purpose.

[0026] In a preferred embodiment, the catalyst is selected from the list consisting of: H-beta, ZSM-5, ZSM-22, MCM-22, mordenite, UZM-9, SAPO (such as SAPO-17, -18, -34, -35, -44, -56) and AlPO, more preferably the catalyst is ZSM-5 or SAPO-34. The catalyst can be fixed to a support material and / or bonded to a binder material. For the present invention, a catalyst fixed to a support material and / or bonded to a binder material is considered a catalyst.

[0027] Although the core structure of some catalysts is also referred to as water adsorbent (e.g., zeolite), the modification that makes these core structures suitable for catalysis has a negative impact on water binding affinity to a large extent. Typically, the active catalytic sites produced on the core structure have acidic properties and are produced by, for example, increasing the ratio of silicon (Si) to aluminum (Al) or introducing phosphorus (P) by contacting with phosphoric acid. These modifications typically eliminate any water adsorption capacity of the catalyst. Vice versa, the water adsorbent has no catalytic activity and has the same core structure as the catalyst. Catalytic sites are not introduced in the water adsorbent. In addition, water adsorption is also affected by temperature, and even if some catalysts may have some residual water adsorption capacity at ambient temperature, this ability does not exist at higher temperatures. When the catalyst is fixed on a carrier or combined with a binder material and the carrier or binder has a certain water adsorption capacity, since the carrier or binder is present in a relatively small amount, the catalyst will not have water adsorption capacity.

[0028] In a preferred embodiment, the maximum water adsorption capacity of the catalyst is less than 0.10 g water / g catalyst at the temperature and pressure in step a), more preferably less than 0.04 g water / g catalyst at the temperature and pressure in step a), even more preferably less than 0.02 g water / g catalyst at the temperature and pressure in step a), most preferably less than 0.01 g water / g catalyst at the temperature and pressure in step a).

[0029] The water adsorption capacity is preferably measured by breakthrough analysis or by thermogravimetric analysis (TGA), preferably by TGA. These two methods are explained in Van Kampen et al. (Adsorption 27, 577-589 (2021)) and Ruthven (Ruthven, DM (1984). Principles of adsorption and adsorption processes. John Wiley & Sons.).

[0030] In the breakthrough analysis, a sample of the catalyst is first dried at 400° C. in an atmosphere not containing water vapor, and subsequently the catalyst is exposed to a gas mixture containing 40 mol % water and an inert tracer at the temperature and pressure in step a) until equilibrium is reached, wherein the time integration of the measured outlet composition yields the amount of water adsorbed. The amount of water adsorbed expressed by weight can be divided by the weight of the catalyst sample to obtain the water adsorption capacity in grams of water / gram of catalyst.

[0031] In the thermogravimetric analysis, a sample of the catalyst is first dried at a temperature of 400° C. in an atmosphere not containing water vapor, the catalyst is subsequently exposed to a gas mixture containing 40 mol % of water at the temperature and pressure in step a) for at least 1000 seconds, and the weight increase of the dried catalyst before and after exposure to the gas mixture containing 40 mol % of water is measured. The water adsorption capacity is the weight increase divided by the weight of the dried catalyst sample.

[0032] The form of the catalyst depends on the reactor size and type. In a preferred embodiment, the catalyst is a granular material, preferably with a particle size between 0.10 mm and 10 cm, more preferably between 0.30 mm and 5.0 cm, and even more preferably between 1.0 cm and 5.0 cm. Typically, the optimal particle size for a fluidized bed reactor is smaller than that for a fixed bed reactor; typically, the optimal particle size for an industrial scale reactor is greater than the optimal particle size for a laboratory reactor. The technician can select the optimal particle size for a particular reactor design. Adsorbent materials capable of absorbing water

[0033] Adsorbent materials capable of adsorbing water are known in the art. Preferably, the adsorbent material capable of adsorbing water is a molecular sieve, more preferably a zeolite, and even more preferably an LTA zeolite. Molecular sieves are materials comprising pores of uniform size. Zeolites are aluminosilicate minerals comprising pores of uniform size. LTA zeolite is a Linde A-type zeolite. Preferably, the adsorbent material capable of adsorbing water is a molecular sieve having a pore size in the range of 1-10 angstroms (A), more preferably in the range of 2-5A, even more preferably in the range of 3-5A, and most preferably in the range of 3-4A. More preferably, the adsorbent material capable of adsorbing water is a zeolite having a pore size in the range of 1-10A, more preferably in the range of 2-5A, even more preferably in the range of 3-5A, and most preferably in the range of 3-4A. Even more preferably, the adsorbent material capable of adsorbing water is an LTA zeolite having a pore size in the range of 1-10A, more preferably in the range of 2-5A, even more preferably in the range of 3-5A, and most preferably in the range of 3-4A.

[0034] In a preferred embodiment, the molar ratio of Si to Al ratio of the adsorbent material capable of adsorbing water is between 0.3:1.0 and 10.0:3.0, more preferably between 0.5:1.0 and 2.0:1.0, most preferably between 0.8:1.0 and 1.2:1.0. Equal amounts of Si and Al indicate a less acidic structure, which is able to adsorb water well. Preferably, the water adsorption capacity of the adsorbent material capable of adsorbing water is at least 0.04 g water / g adsorbent material at the temperature and pressure in step a), more preferably at least 0.06 g water / g adsorbent material at the temperature and pressure in step a), even more preferably at least 0.08 g water / g adsorbent material at the temperature and pressure in step a), most preferably at least 0.10 g water / g adsorbent material at the temperature and pressure in step a).

[0035] For the catalyst, the water adsorption capacity is preferably measured by breakthrough analysis or by thermogravimetric analysis (TGA), preferably by TGA. These two methods are explained in Van Kampen et al. (Adsorption 27, 577-589 (2021)) and Ruthven (Ruthven, DM (1984). Principles of adsorption and adsorption processes. John Wiley & Sons.).

[0036] In the breakthrough analysis, a sample of the adsorbent material capable of absorbing water is first dried at 400° C. in an atmosphere not containing water vapor, and then the adsorbent material capable of absorbing water is exposed to a gas mixture comprising 40 mol % water and an inert tracer at the temperature and pressure in step a) until equilibrium is reached, wherein the measured outlet composition is integrated over time to yield the amount of water adsorbed. The amount of water adsorbed, expressed in weight, can be divided by the weight of the sample of the adsorbent material capable of absorbing water to obtain the water adsorption capacity in grams of water per gram of the adsorbent material capable of absorbing water.

[0037] In the thermogravimetric analysis, a sample of the adsorbent material capable of absorbing water is first dried at a temperature of 400° C. in an atmosphere not containing water vapor, and then the adsorbent material capable of absorbing water is exposed to a gas mixture containing 40 mol % of water at the temperature and pressure in step a) for at least 1000 seconds, and the weight increase of the dried adsorbent material capable of absorbing water before and after exposure to the gas mixture containing 40 mol % of water is measured. The water adsorption capacity is the weight increase divided by the original weight of the dried adsorbent material capable of absorbing water.

[0038] In a preferred embodiment, the catalyst and the adsorbent material capable of absorbing water are not bonded to each other. Bonding may reduce the catalytic activity of the catalyst and / or the water adsorption capacity of the adsorbent material. In addition, bonding is expensive and provides less freedom in selecting the ratio of catalyst to adsorbent material capable of absorbing water.

[0039] In a preferred embodiment, the weight ratio of the catalyst to the adsorbent material capable of adsorbing water is between 1.0:10.0 and 10.0:1.0, more preferably between 1.0:10.0 and 5.0:1.0, even more preferably between 1.0:10.0 and 2.0:1.0, and most preferably between 1.0:5.0 and 1.0:1.0. Within these ratios, good water adsorption capacity is obtained at sufficient reaction rates.

[0040] The form of the adsorbent material capable of absorbing water depends on the reactor size and type. In a preferred embodiment, the adsorbent material capable of absorbing water is a granular material, preferably with a particle size between 0.10 mm and 10 cm, more preferably between 0.30 mm and 5.0 cm, even more preferably between 1.0 cm and 5.0 cm. Typically, the optimal particle size for a fluidized bed reactor is smaller than for a fixed bed reactor; typically, the optimal particle size for an industrial scale reactor is larger than the optimal particle size for a laboratory reactor. A skilled person is able to select the optimal particle size for a particular reactor design.

[0041] In a preferred embodiment, the adsorbent material capable of adsorbing water comprises water in an amount of less than 0.10 g water / g adsorbent material at the temperature and pressure in step a), even more preferably less than 0.04 g water / g adsorbent material at the temperature and pressure in step a), even more preferably less than 0.02 g water / g adsorbent material at the temperature and pressure in step a), most preferably less than 0.01 g water / g adsorbent material at the temperature and pressure in step a). Purge gas

[0042] In a preferred embodiment, the purge gas is air, nitrogen, hydrogen or a hydrocarbon gas, more preferably air. Preferably, the purge gas contains less than 5.0 mol% water, preferably less than 1.0 mol% water, most preferably less than 0.5 mol% water based on the total amount of the purge gas. method

[0043] Aspects of the invention relate to a method for converting oxygenates into hydrocarbons. The method comprises a reaction step a), in which a reaction product is formed, and a regeneration step b), in which an adsorbent material capable of absorbing water is regenerated. The regeneration of the adsorbent material capable of absorbing water involves desorbing water from the adsorbent material. In this way, the adsorbent material is ready for the next reaction step a) to adsorb water. During the reaction step a), in addition to forming a reaction product, water is also adsorbed by the adsorbent material capable of absorbing water.

[0044] The present invention relates to contacting in a reactor. In a preferred embodiment, the contacting is carried out by providing a feed, more preferably by providing a continuous feed. In a preferred embodiment, the contacting is carried out by providing a feed and the feed is a feed gas.

[0045] In a preferred embodiment, the temperature in step a) is between 200°C and 500°C, more preferably between 200°C and 400°C, even more preferably between 200°C and 350°C, most preferably between 225°C and 275°C. This temperature is lower than that of conventional processes. The inventors surprisingly found that even at these lower temperatures, excellent conversions can be achieved. Furthermore, the lower temperatures provide slower or even no coke formation. Typically, the catalyst is deactivated due to coke formation. In a preferred embodiment, the oxygenate is DME and the temperature in step a) is between 200°C and 500°C, more preferably between 200°C and 400°C, even more preferably between 200°C and 350°C, most preferably between 225°C and 275°C, or the oxygenate is methanol and the temperature in step a) is between 200°C and 500°C, more preferably between 275°C and 400°C, even more preferably between 300°C and 400°C, most preferably between 300°C and 350°C.

[0046] In a preferred embodiment, the pressure in step a) is between 1.0 and 30 absolute bar, more preferably between 1.0 and 20 absolute bar, even more preferably between 2.0 and 10 absolute bar, and most preferably between 4.0 and 8.0 absolute bar. The choice of pressure in step a) is related to several aspects. The higher pressure in step a) makes the pressure difference between step a) and step b) larger, which is beneficial to the water desorption in step b) when pressure is selected as the driving force for water desorption. Such pressure fluctuation operation is generally an effective way to operate the method according to the present invention, because the pressure drop can be achieved in a short time span and relatively less energy is used. Since water is removed during the reaction step, which is not the case for conventional methods, increasing the pressure tends to affect the conversion rate to a lesser extent. It has been reported that in some cases pressure can affect selectivity. In the art, methods for converting oxygenated compounds into hydrocarbons are typically operated at ambient pressure, but operating pressures up to 30 absolute bar have also been reported.

[0047] The conditions in the reactor between step a) and step b) differ in temperature, pressure and / or feed gas composition. This is typical for a fluctuating process. The water holding capacity of the adsorbent depends on temperature and pressure. During the regeneration step b), the reactor undergoes changes in temperature, pressure and / or feed gas composition to effectively desorb water from the adsorbent material. The purge gas in step b) carries the water away. In a preferred embodiment, the temperature in step b) is at least 100°C higher than the temperature in step a) and / or the pressure in step b) is at least 0.9 bar lower than the pressure in step a), more preferably the temperature in step b) is at least 150°C higher than the temperature in step a) and / or the pressure in step b) is at least 3.0 bar lower than the pressure in step a), even more preferably the temperature in step b) is at least 200°C higher than the temperature in step a) and / or the pressure in step b) is at least 5.0 bar lower than the pressure in step a). In a preferred embodiment, the temperature in step b) is at least 100° C. higher than the temperature in step a), more preferably the temperature in step b) is at least 150° C. higher than the temperature in step a), even more preferably the temperature in step b) is at least 200° C. higher than the temperature in step a). In a preferred embodiment, the pressure in step b) is at least 0.9 bar lower than the pressure in step a), more preferably the pressure in step b) is at least 3.0 bar lower than the pressure in step a), even more preferably the pressure in step b) is at least 5.0 bar lower than the pressure in step a).

[0048] In a preferred embodiment, the temperature in step b) is between 200°C and 500°C, more preferably between 200°C and 400°C, even more preferably between 200°C and 350°C, most preferably between 225°C and 275°C. In case the process comprises temperature fluctuations, preferably the temperature in step b) is between 300°C and 700°C, more preferably between 400°C and 600°C, even more preferably between 400°C and 500°C. In a preferred embodiment, the pressure in step b) is between 1.0 and 30 bar, more preferably between 1.0 and 20 bar, even more preferably between 2.0 and 10 bar, most preferably between 4.0 and 8.0 bar. In case the process comprises pressure fluctuations, preferably the pressure in step b) is between 2.0 and 20 bar, more preferably between 1.0 and 10 bar, even more preferably between 0.5 and 5 bar, most preferably between 0.1 and 2 bar.

[0049] In a preferred embodiment, the method operates cyclically, wherein step b) is followed by another occurrence of step a). In this way, the reactor of the method alternates between mode a) and mode b), optionally in combination with another mode. Considering the manufacturing equipment, a continuous method is preferred, and the method preferably includes two or more reactors, more preferably three or more reactors, which contain a catalyst and an adsorbent material capable of adsorbing water. For this embodiment, preferably, at least one of the two or three or more reactors is in mode a). By having two or more reactors, one reactor can be in reaction mode a), while another reactor is in regeneration mode b). When the adsorbent material capable of adsorbing water in the reactor in reaction mode a) is saturated with water, the feed stream can be switched to the reactor in regeneration mode b) and the reaction can continue in the reactor; therefore, the reactor enters reaction mode a). At the same time, the reactor containing the water-saturated adsorbent material can enter regeneration mode b). In this way, a continuous feed stream and product stream can be maintained. In some cases, mode a) and mode b) do not have equal lengths. Therefore, in a preferred embodiment, the method includes step c) idle mode. During idle mode, no gas is fed into the reactor.

[0050] The inventors have found that for the process of the present invention, coking of the catalyst tends to occur little or no. This can reduce or even eliminate the need for catalyst decoking. Without being bound by theory, the inventors believe that lower temperatures and / or removal of water during the reaction and / or intermittent adsorbent regeneration have a positive effect on coke formation. There may still be situations where the catalyst needs to be decoked. During catalyst decoking, the coke is removed by contacting the catalyst with an oxygen-containing gas at a temperature above 400°C, preferably above 500°C, more preferably above 600°C. In a preferred embodiment, the process of the present invention comprises step d) decoking the catalyst by contacting it with an oxygen-containing gas at a temperature above 400°C, preferably above 500°C, more preferably above 600°C. In a preferred embodiment, the catalyst is decoked in a reactor comprising the catalyst and an adsorbent material capable of adsorbing water. In this way, catalyst decoking and adsorbent regeneration are carried out simultaneously. For this embodiment, preferably the reactor is a fixed bed reactor. Preferably, the method is operated cyclically, wherein step b) is followed by step a) and step d) is performed at most once every 3 cycles, more preferably at most once every 6 cycles, most preferably at most once every 9 cycles.

[0051] In an alternative preferred embodiment, the catalyst is decoked in a separate decoking reactor. For this embodiment, preferably the reactor is a fluidized bed reactor. Reactor

[0052] Furthermore, the present invention relates to a fluidized bed or fixed bed reactor for converting oxygenates into hydrocarbons, the reactor comprising a catalyst for converting oxygenates into hydrocarbons and an adsorbent material capable of adsorbing water, wherein the catalyst and the adsorbent material are different. In a preferred embodiment, the present invention relates to 2 or more of these reactors. Preferably the reactor is a fixed bed reactor.

[0053] In a preferred embodiment, the catalyst is selected from the list consisting of: H-beta, ZSM-5, ZSM-22, MCM-22, mordenite, UZM-9, SAPO (such as SAPO-17, -18, -34, -35, -44, -56) and AlPO, preferably the catalyst is ZSM-5 or SAPO-34. In a preferred embodiment, the adsorbent material capable of adsorbing water is a molecular sieve with a pore size in the range of 2-5A, more preferably a zeolite with a pore size in the range of 2-5A, and even more preferably an LTA zeolite with a pore size in the range of 2-5A.

[0054] In a preferred embodiment, the weight ratio of catalyst to adsorbent material capable of absorbing water is between 1.0:10.0 and 10:1.0, preferably between 1.0:10.0 and 5.0:1.0. In a preferred embodiment, the water adsorption capacity of the adsorbent material capable of absorbing water is at least 0.04 g water / g adsorbent material at the temperature and pressure in step a), preferably at least 0.06 g water / g adsorbent material at the temperature and pressure in step a), more preferably at least 0.08 g water / g adsorbent material at the temperature and pressure in step a), most preferably at least 0.10 g water / g adsorbent material at the temperature and pressure in step a).

[0055] In a preferred embodiment, the water adsorption capacity of the catalyst is less than 0.10 g water / g catalyst at the temperature and pressure of step a), preferably less than 0.04 g water / g catalyst at the temperature and pressure of step a). In a preferred embodiment, the catalyst and the adsorbent material capable of adsorbing water are not combined with each other.

[0056] In a preferred embodiment, the oxygenate is one or more of: methanol (MeOH), ethanol (EtOH), isopropanol (IPA), n-butanol (BuOH), gasoline grade tert-butyl alcohol (GTBA), methyl tert-butyl ether (MTBE), tert-amyl methyl ether (TAME), tert-hexyl methyl ether (THEME), ethyl tert-butyl ether (ETBE), tert-amyl ethyl ether (TAEE), dimethyl ether (DME) or diisopropyl ether (DIPE), preferably the oxygenate is methanol and / or dimethyl ether, more preferably the oxygenate is methanol. In a preferred embodiment, the hydrocarbon is selected from the group consisting of olefins, alkanes, aromatic compounds and any combination thereof, wherein preferably the olefin is one or more of ethylene, propylene, 1-butene, 2-butene, and isobutylene, the alkane is one or more of alkanes containing 2 to 18 carbon atoms, and the aromatic compound is one or more of benzene, toluene and xylene. use

[0057] The present invention also relates to the use of an adsorbent material capable of adsorbing water for converting oxygenates into hydrocarbons in the presence of a catalyst for converting oxygenates into hydrocarbons, wherein the catalyst and the adsorbent material are different, preferably wherein the use involves one or more of the following: - Increased conversion compared to the absence of adsorbent material, - the lifetime of the catalyst is extended compared to when no adsorbent material is present, - reduced deactivation of the catalyst compared to when no adsorbent material is present, - an increase in the reaction rate compared to when no adsorbent material is present, and - The need for catalyst decoking is reduced, preferably avoided, compared to when no adsorbent material is present. Preferably, the increase, prolongation and / or decrease is compared to when no adsorbent material is present and the same amount of catalyst is present.

[0058] Thus, in one embodiment, the present invention relates to the use of an adsorbent material capable of adsorbing water for increasing the conversion of oxygenates to hydrocarbons in the presence of a catalyst for converting oxygenates to hydrocarbons, wherein the catalyst and the adsorbent material are different and the increase is compared to the absence of the adsorbent material.

[0059] In another embodiment, the present invention is directed to the use of an adsorbent material capable of adsorbing water for increasing the life of a catalyst in a process for converting oxygenates to hydrocarbons in the presence of a catalyst for converting oxygenates to hydrocarbons, wherein the catalyst and the adsorbent material are different and the increase is compared to when the adsorbent material is not present.

[0060] In another embodiment, the present invention is directed to the use of an adsorbent material capable of adsorbing water for reducing deactivation of the catalyst in a process for converting oxygenates to hydrocarbons in the presence of a catalyst for converting oxygenates to hydrocarbons, wherein the catalyst and the adsorbent material are different and the reduction is compared to when the adsorbent material is not present.

[0061] In another embodiment, the present invention is directed to the use of an adsorbent material capable of adsorbing water for increasing the reaction rate in a process for converting oxygenates to hydrocarbons in the presence of a catalyst for converting oxygenates to hydrocarbons, wherein the catalyst and the adsorbent material are different and the increase is compared to when the adsorbent material is not present.

[0062] In another embodiment, the present invention is directed to the use of an adsorbent material capable of adsorbing water for reducing the need for catalyst decoking in a process for converting oxygenates to hydrocarbons in the presence of a catalyst for converting oxygenates to hydrocarbons, wherein the catalyst and the adsorbent material are different and the reduction is compared to when the adsorbent material is not present.

[0063] In a preferred embodiment, the catalyst is selected from the list consisting of: H-beta, ZSM-5, ZSM-22, MCM-22, mordenite, UZM-9, SAPO (such as SAPO-17, -18, -34, -35, -44, -56) and AlPO, preferably the catalyst is ZSM-5 or SAPO-34. In a preferred embodiment, the adsorbent material capable of adsorbing water is a molecular sieve with a pore size in the range of 2-5A, more preferably a zeolite with a pore size in the range of 2-5A, and even more preferably an LTA zeolite with a pore size in the range of 2-5A.

[0064] In a preferred embodiment, the weight ratio of catalyst to adsorbent material capable of absorbing water is between 1.0:10.0 and 10:1.0, preferably between 1.0:10.0 and 5.0:1.0. In a preferred embodiment, the water adsorption capacity of the adsorbent material capable of absorbing water is at least 0.04 g water / g adsorbent material at the temperature and pressure in step a), preferably at least 0.06 g water / g adsorbent material at the temperature and pressure in step a), more preferably at least 0.08 g water / g adsorbent material at the temperature and pressure in step a), most preferably at least 0.10 g water / g adsorbent material at the temperature and pressure in step a).

[0065] In a preferred embodiment, the water adsorption capacity of the catalyst is less than 0.10 g water / g catalyst at the temperature and pressure of step a), preferably less than 0.04 g water / g catalyst at the temperature and pressure of step a). In a preferred embodiment, the catalyst and the adsorbent material capable of adsorbing water are not combined with each other.

[0066] In a preferred embodiment, the oxygenate is one or more of: methanol (MeOH), ethanol (EtOH), isopropanol (IPA), n-butanol (BuOH), gasoline grade tert-butyl alcohol (GTBA), methyl tert-butyl ether (MTBE), tert-amyl methyl ether (TAME), tert-hexyl methyl ether (THEME), ethyl tert-butyl ether (ETBE), tert-amyl ethyl ether (TAEE), dimethyl ether (DME) or diisopropyl ether (DIPE), preferably the oxygenate is methanol and / or dimethyl ether, more preferably the oxygenate is methanol. In a preferred embodiment, the hydrocarbon is selected from the group consisting of olefins, alkanes, aromatic compounds and any combination thereof, wherein preferably the olefin is one or more of ethylene, propylene, 1-butene, 2-butene, and isobutylene, the alkane is one or more of alkanes containing 2 to 18 carbon atoms, and the aromatic compound is one or more of benzene, toluene and xylene.

[0067] In a preferred embodiment, the use is carried out in a fluidized bed reactor or a fixed bed reactor, preferably in a fixed bed reactor. In a preferred embodiment, the use is carried out at a temperature between 200°C and 500°C, preferably between 200°C and 400°C, even more preferably between 200°C and 350°C, most preferably between 225°C and 275°C. In a preferred embodiment, the use is carried out at a pressure between 1.0 and 30 absolute bar, preferably between 1.0 and 20 absolute bar. General Definition

[0068] In this document and its claims, the verb "to comprise" and its conjugations are used in its non-limiting sense to mean including the items following the word, but not excluding items not specifically mentioned. In addition, reference to an element by the indefinite article "a / an" does not exclude the possibility that more than one element is present, unless the context clearly requires the presence of one and only one element. Thus, the indefinite article "a" or "an" generally means "at least one". The word "about" or "approximately", when used in conjunction with a numerical value (e.g., about 10), preferably means that the value can be a given value plus or minus 1% of that value.

[0069] The invention has been described above with reference to a number of exemplary embodiments. Modifications and alternative embodiments of some parts or elements are possible and are included within the scope of protection as defined by the appended claims. All references to literature and patent documents are hereby incorporated by reference.

[0070] Absolute bar stands for bar (absolute value) and relates to the pressure relative to a perfect vacuum as a zero reference. 1 bar is 100,000 N / m 2 . 1 bar is 100,000 Pascals. In the context of the present invention and in particular in the context of 'use of an adsorbent material capable of adsorbing water for converting oxygenates into hydrocarbons in the presence of a catalyst for converting oxygenates into hydrocarbons', 'in the presence of' means that the catalyst and the adsorbent material are present in the same reactor. BRIEF DESCRIPTION OF THE DRAWINGS

[0071] Figure 1a The output concentrations of DME, helium and water are plotted over time for a cyclic operating method according to the invention. The output concentrations were measured by mass spectrometry. Figure 1a 3rd cycle from the start of the reaction. Concentrations were measured by mass spectrometry. Time (in minutes) was plotted on the X-axis. The measured intensity was plotted on the Y-axis. The black solid line is the helium signal (m / z=4), the gray dashed line with long dashes is the DME signal (m / z=45), and the black dashed line with short dashes is the water signal (m / z=18). The DME signal shows a peak at about 296.3 minutes.

[0072] Figure 1b The output concentrations of DME, helium and water are plotted over time for a cyclic operating method according to the invention. The output concentrations were measured by mass spectrometry. Figure 1b50th cycle from the start of the reaction. Concentration was measured by mass spectrometry. Time (in minutes) was plotted on the X-axis. The measured intensity was plotted on the Y-axis. The black solid line is the helium signal (m / z=4), the gray dashed line with a long dash is the DME signal (m / z=45), and the gray solid line is the water signal (m / z=18). The water signal remains below an intensity level of 1.00E-09. The DME signal shows a peak at about 4682.3 minutes. Examples Example 1 - Conversion of oxygenated compounds method

[0073] A quartz reactor with an inner diameter of 16 mm was filled with 2.5 g of catalyst and 6.0 g of water adsorbent to give a bed height of about 70 mm. During adsorption, the adsorption was carried out at 250 °C and 1 absolute bar at a rate of 92 Nml min -1 Feed into the reactor. The gas mixture contains 5 mol% DME, 5 mol% He (as a tracer) and the balance Ar. Regeneration is performed by switching the gas flow to 100 mol% Ar and increasing the temperature to 400°C for 60 minutes. Reactor outlet gas analysis is performed continuously by a Pfeiffer Thermostar mass spectrometer.

[0074] As for the materials, a mixture consisting of an adsorbent and a catalyst (SAPO or HZSM-5) was used. The materials used were: Water adsorbent: 3A molecular sieve, ASGE Catalyst 1: SAPO-34, Zeolyst Catalyst 2: Zeolite HZSM-5, PQ Chemicals

[0075] For the experiment, a particle size of 0.212-0.425 mm was used. Adsorbent (3A) is available in the form of small pellets. By crushing and sieving, an accurate particle size was obtained. Both catalysts are available as fine powders. In order to obtain a suitable particle size, these powders were first granulated using a manual press. The tablets were then crushed and sieved again. 6.0 g of adsorbent particles were fully mixed with 2.5 g of SAPO-34 or HZSM-5. After mixing, a quartz reactor with an internal diameter of 16 mm was filled to obtain a typical bed height of about 70 mm. result

[0076] The product mixture was subjected to mass spectrometry analysis and the peaks were assigned according to Wallace, WE (2018). Mass spectra. NIST Chemistry WebBook, NIST Standard Reference Database [mass spectrometry, NIST chemical network book, NIST standard reference database], (69). In Table 1, the substances analyzed and their corresponding m / z values ​​are summarized. Table 2 summarizes the values ​​of each m / z before and after breakthrough at a specific time. Table 1. Mass spectrometer responses and peak identities Table 2. Pre- and post-penetration product distribution (pre- and post-penetration intensities normalized to helium, He (at t = 0) = 100) Discussion and Conclusion

[0078] Both experiments involved DME dehydration experiments over SAPO and HZSM5 catalysts, much like the experiments performed conventionally. The reaction temperature was relatively low. The difference was the presence of a water adsorbent, which affected the reactor performance and produced a transient response.

[0079] Basically, the experiment can be divided into pre-breakthrough and post-breakthrough periods. The pre-breakthrough period starts at t=0 and ends when the water signal starts to increase. This increase indicates that water starts to pass through the reactor and the 3A water adsorbent: the adsorbent becomes saturated. The post-breakthrough period includes two stages, first the water concentration in the reaction product increases logarithmically until a plateau is reached. For Experiment 1, the pre-breakthrough period ends at about 28 minutes and the plateau is reached at about 65 minutes; for Experiment 2, the pre-breakthrough period ends at about 4 minutes and the plateau is reached at about 33 minutes.

[0080] Before water breakthrough, the concept of adsorption enhancement applies: adsorption removes water from the gas phase in the reactor, resulting in a change or enhancement in DME conversion. As shown in Table 2, for Experiments 1 and 2, the amount of oxygenates DME and methanol leaving the reactor was very low.

[0081] The plateau represents a 'conventional' response because the effect of the adsorbent is effectively offset. Although mass spectrometer signals are not quantitative, they can be compared relative to each other. For experiments 1 and 2, the response clearly shows that the DME (and methanol) conversion rate before breakthrough is significantly improved compared to after breakthrough. In the period before breakthrough, experiment 1 shows a high response of, for example, m / z values ​​of 41 and 55, indicating the formation of hydrocarbons (olefins and / or paraffins). Experiment 2 shows that this effect is even more obvious, wherein the m / z values ​​of 41, 43 and 55 before breakthrough are higher than their respective responses after breakthrough. In all cases, after water breakthrough, the DME response increases strongly, which indicates that the DME conversion rate decreases significantly. The low conversion rate of the conventional method without adsorption is not unexpected, because the temperature of 250°C is quite low for DME (and methanol) dehydration experiments.

[0082] In summary, Experiments 1 and 2 show the effect of adsorption enhancement. Almost complete conversion of DME can be achieved before breakthrough, and hydrocarbon products are formed. Post-breakthrough conditions show incomplete conversion and slightly altered product spectra. Therefore, adsorption enhancement significantly increases conversion and enables lower reaction temperatures. Example 2 - Absence of Water Adsorption by SAPO34 Catalyst

[0083] The SAPO34 catalyst of Example 1 was tested for water adsorption. 0.5 g of SAPO34 catalyst (sieve fraction 212-425 μm) was placed in a reactor with a diameter of 6 mm and the temperature was brought to 250° C. The pressure in the reactor was 1 absolute bar. A gas stream (92 Nml min -1 ) was provided to the reactor, and the gas stream from the reactor was analyzed as in Example 1. The penetration of the water front was instantaneous, and in less than a minute, the water concentration in the outflow stream reached a constant, indicating that no water adsorption occurred. The steady-state flow was maintained for about 22 minutes, and thereafter the temperature was increased to 400° C. and a gas stream free of water was provided. The subsequent decrease in the water concentration in the outflow stream was instantaneous, and again no water peak typical for water-absorbing materials was observed, indicating that the SAPO34 catalyst did not adsorb water. Example 3 - Absence of Catalyst Deactivation by Coke Formation method

[0084] For Example 3, the water adsorbent combination of Experiment 1 was used (zeolite HZSM-5 (PQ Chemicals) and molecular sieve type 3A (ASGE); the sieve fractions were both 212-425 μm). A quartz reactor with an inner diameter of 10 mm was filled with 0.5 g of catalyst and 2.5 g of water adsorbent to obtain a bed height of about 58 mm. However, instead of monitoring one cycle, the reactor was operated alternately in reaction mode and adsorbent regeneration mode. The reaction mode was as described in Example 1, with a temperature of 250° C. and a pressure of 1 absolute bar. The adsorbent regeneration mode was at 400° C. and 1 absolute bar. As in Example 1, during the adsorption period, 92 Nml min -1 Feed in the reactor.Gas mixture contains 5mol%DME, 5mol%He (as tracer) and surplus Ar.Purge gas is Ar.Reaction time is 15 minutes and regeneration time is 45 minutes.Reactor outlet gas analysis is carried out continuously by Pfeiffer Thermostar mass spectrometer.At the beginning of reaction mode, after adsorbent regeneration mode, to reactor feed DME and improve helium inlet concentration (step change).At the outlet of reactor, the concentration of reaction product and unconverted feed gas is measured in time.For the sake of clarity, only the outlet concentration of helium, DME and water is drawn. Results and Conclusions

[0085] The purpose of this experiment is to study the effect of the method of the present invention on catalyst deactivation. Figure 1a In Figure 1, the outlet concentrations of DME (m / z 45), He (m / z 4), and water (m / z 18) are plotted as a function of time for the third cycle. Figure 1b In the figure, the 50th cycle is plotted.

[0086] According to the performance of DME conversion rate evaluation system.As in Example 1 and Example 2, the penetration that increases helium concentration is followed by the period when all DME are converted, until DME also penetrates, followed by water penetration.The DME local peak that can be observed immediately after DME penetrates and the difference of the breakthrough time between DME and water are not further studied, but temporarily attributed to dynamic ' roll up (roll up) ' effect (as for example at Yang, RT (1997). Gas separation by adsorption processes [carry out gas separation by adsorption method] (volume 1). World Scientific [world science and technology publishing company]. discussed).

[0087] For cycle 3, the He signal is stable and increases at t=295.7 minutes, indicating the end of the regeneration mode and the beginning of the reaction mode. The breakthrough of DME is at 296.2 minutes; 0.42 minutes after the reaction mode begins. For cycle 50, the He signal is stable and increases at t=4681.8 minutes, indicating the end of the regeneration mode and the beginning of the reaction mode. The breakthrough of DME is at 4682.2 minutes; 0.43 minutes after the reaction mode begins.

[0088] Essentially, the DME conversion (as derived from the difference in breakthrough time between the helium step change and the DME signal) unexpectedly remained constant between cycles 3 and 50. Thus, no measurable drop in DME conversion was observed over the 70 hours of repeated cycling, from which it can be concluded that the catalyst activity remained constant. Example 4 - Effect of adsorption enhancement on SAPO-34 stability and conversion. method

[0089] The reaction was carried out in a quartz reactor connected to a Pfeiffer Thermostar mass spectrometer (MS) for reactor outlet gas analysis. The measurement settings were the same as in Examples 1-3. Three experiments were performed. In the first and second experiments, a quartz reactor with an inner diameter of 13 mm was filled only with catalyst, while in the third experiment, a quartz reactor with an inner diameter of 18 mm was filled with a mixture of catalyst and water adsorbent. The materials used are as follows: Water adsorbent: 3A molecular sieve, ASGE Catalyst: SAPO-34, Zeolyst

[0090] For all experiments, the particle size of catalyst and adsorbent is 0.212-0.425mm. Adsorbent (3A) is available in the form of small pellets. By crushing and sieving, accurate particle size is obtained. Catalyst is available as fine powder. In order to obtain suitable particle size, the powder is first granulated using a manual press. The tablets are then crushed and sieved again. For the first experiment, a quartz reactor with an inner diameter of 13mm was filled with 2.54g of SAPO-34 catalyst to obtain a bed height of 37mm. Similarly, for the second experiment, a quartz reactor with an inner diameter of 13mm was filled with 2.501g of SAPO-34 catalyst to obtain a bed height of 39mm. For the third experiment, 6.035g of adsorbent particles were fully mixed with 2.507 grams of SAPO-34 catalyst. After mixing, a quartz reactor with an inner diameter of 18mm was filled to obtain a bed height of 54mm.

[0091] During adsorption, the adsorption rate was 91.6 Nml min in all experiments. -1The gas mixture contained 5 mol% DME, 5 mol% He (as a tracer) and the balance Ar for all three experiments. Experiments 1 and 2 (reactor beds consisting of only SAPO-34 catalyst) were conducted at two temperatures, 450°C and 250°C. Experiment 3 (reactor bed consisting of a mixture of SAPO-34 catalyst and 3A zeolite water adsorbent) was conducted at 250°C.

[0092] Experiment 3 was conducted in a cyclic mode, where regeneration was performed by switching the gas flow to 90 mol% Ar and 10 mol% He, and raising the temperature to 400° C. The reaction time was 60 minutes for each cycle. For all experiments, the composition of the gas leaving the reactor was measured as in Example 1. In this way, water, DME and hydrocarbon concentrations can be tracked over time. Results and Discussion

[0093] The difference between Experiment 1 and Experiment 2 is the operating temperature. In Experiment 1, at 450°C, the conversion slowly decreases during the first 30 hours, which is noticeable by a gradual decrease in the hydrocarbon concentration in the outlet stream (about 20%). After about 30 hours, the reaction suddenly stops, marked by a sharp increase in the DME signal and a drop in the olefin concentration to 0. This indicates a complete deactivation of the catalyst. Although the conversion appears to be stable during the first 30 hours, catalyst deactivation also occurs. However, due to the excess catalyst, this could not be confirmed in the outlet stream.

[0094] In Experiment 2, at 250°C, there was an almost instantaneous loss of activity. Immediately after starting the DME feed, there was a significant amount of DME in the reaction product (about 30% of the feed amount), indicating incomplete conversion. Olefins were formed. The DME concentration gradually increased over time, and the olefin concentration gradually decreased, until after about 20 hours, the DME concentration stabilized at the input concentration, and the hydrocarbon concentration was zero. This indicated complete deactivation of the catalyst. The relatively low initial conversion was not unexpected, as the temperature of 250°C is quite low for DME (and methanol) dehydration experiments. Both experiments demonstrated relatively rapid and complete deactivation of the catalyst.

[0095] The main difference between the first two experiments and the third one is the presence of the water adsorbent, which affects the reactor performance and produces a transient response. When the water signal starts to increase significantly, it indicates that water starts to pass through the reactor and the water adsorbent becomes saturated; at the same time, the DME response increases strongly, which indicates that the DME conversion rate decreases. Before water breakthrough, the concept of adsorption enhancement applies. The adsorbent removes water from the gas phase, resulting in a change or enhancement in the DME conversion rate.

[0096] For the third experiment, at 250°C in the presence of a water adsorbent, the conversion of DME was significantly higher than in the case where only a catalyst was present (i.e., Experiment 2). For the first 12 cycles, after switching to the DME feed, all DME was converted to hydrocarbons, which was noted by the absence of any DME in the outlet stream. Even after 30 cycles (about 90 hours), the DME conversion was still about 50%. After 65 cycles (about 190 hours), the DME conversion dropped to about 25%, after which it stabilized at this level of 25% (measured up to 125 cycles).

[0097] Comparing the 2nd and 3rd experiments, it can be concluded that the method of the present invention provides higher conversion and longer catalyst stability. In addition, we note that the 3rd experiment has not been optimized. The regeneration of the adsorbent may not be complete, resulting in a lower adsorption capacity and thus a decrease in DME conversion over time. In addition, the reaction continues after the adsorbent is saturated (noticeable by the gradual increase in water concentration in the outlet stream), which is due to the cycle time being much longer than the time required to saturate the adsorbent. This may lead to catalyst deactivation.

[0098] In summary, the experiments demonstrate that in the presence of an adsorbent, the catalyst activity remains longer even at lower temperatures (250° C. vs. 450° C.). In addition, and equally important, the introduction of an adsorbent in a process for converting oxygenates to hydrocarbons significantly increases the conversion rate.

Claims

1. Use of an adsorbent material capable of adsorbing water for converting oxygenates into hydrocarbons in the presence of a catalyst for converting oxygenates into hydrocarbons, wherein the catalyst and the adsorbent material are different, preferably wherein the use involves one or more of the following: - an increase in conversion compared to the absence of the adsorbent material, - the lifetime of the catalyst is extended compared to the absence of the adsorbent material, - the deactivation of the catalyst is reduced compared to the absence of the adsorbent material, - an increase in the reaction rate compared to the absence of the adsorbent material, and - The need for catalyst decoking is reduced, preferably avoided, compared to when the adsorbent material is not present.

2. A method for converting oxygenates into hydrocarbons, the method comprising: a) contacting a catalyst with the oxygenate in the presence of an adsorbent material capable of adsorbing water in a reactor to form the hydrocarbon; and subsequently b) regenerating the adsorbent material in the same reactor by contacting the adsorbent material with a purge gas; The catalyst and adsorbent materials are different.

3. The method according to claim 2, wherein: The method operates cyclically, wherein step b) is followed by step a).

4. The method according to claim 2 or 3, wherein: The temperature in step a) is between 200 and 500°C, preferably between 200 and 400°C, even more preferably between 200 and 350°C, most preferably between 225 and 275°C.

5. The method according to any one of claims 2 to 4, wherein: The pressure in step a) is between 1.0 and 30 absolute bar, preferably between 1.0 and 20 absolute bar.

6. The method according to any one of claims 2 to 5, wherein: The temperature in step b) is at least 100°C higher than the temperature in step a) and / or wherein the pressure in step b) is at least 0.9 bar lower than the pressure in step a), preferably wherein the temperature in step b) is at least 150°C higher than the temperature in step a) and / or wherein the pressure in step b) is at least 3.0 bar lower than the pressure in step a).

7. The process according to any one of claims 2 to 6, having two or more reactors comprising the catalyst and the adsorbent material capable of adsorbing water, preferably wherein at least one of the two or more reactors performs step a).

8. The method according to any one of claims 2 to 7, wherein: The catalyst is selected from the list consisting of H-beta, ZSM-5, ZSM-22, MCM-22, mordenite, UZM-9, SAPO (such as SAPO-17, -18, -34, -35, -44, -56) and A1PO, preferably the catalyst is ZSM-5 or SAPO-34.

9. The method according to any one of claims 2 to 8, wherein: The adsorbent material capable of adsorbing water has a pore size of Molecular sieves with a pore size in the range of The zeolite having a pore size in the range of LTA zeolites within the range.

10. The method according to any one of claims 2 to 9, wherein: The weight ratio of catalyst to adsorbent material capable of adsorbing water is between 1.0:10.0 and 10.0:1.0, preferably between 1.0:10.0 and 5.0:1.

0.

11. The method according to any one of claims 2 to 10, wherein: The adsorbent material capable of adsorbing water has a water adsorption capacity of at least 0.04 g water / g adsorbent material at the temperature and pressure in step a), preferably at least 0.06 g water / g adsorbent material at the temperature and pressure in step a), more preferably at least 0.08 g water / g adsorbent material at the temperature and pressure in step a), most preferably at least 0.10 g water / g adsorbent material at the temperature and pressure in step a).

12. The method according to any one of claims 2 to 11, wherein: The water adsorption capacity of the catalyst is less than 0.10 g of water / g of catalyst at the temperature and pressure of step a), preferably less than 0.04 g of water / g of catalyst at the temperature and pressure of step a).

13. The method according to any one of claims 2 to 12, wherein: The oxygen-containing compound is one or more of the following: methanol (MeOH), ethanol (EtOH), isopropanol (IPA), n-butanol (BuOH), gasoline-grade tert-butyl alcohol (GTBA), methyl tert-butyl ether (MTBE), tert-amyl methyl ether (TAME), tert-hexyl methyl ether (THEME), ethyl tert-butyl ether (ETBE), tert-amyl ethyl ether (TAEE), dimethyl ether (DME) or diisopropyl ether (DIPE), preferably the oxygen-containing compound is methanol and / or dimethyl ether, more preferably the oxygen-containing compound is methanol.

14. The method according to any one of claims 2 to 13, wherein: The hydrocarbon is selected from the group consisting of olefins, alkanes, aromatic compounds and any combination thereof, wherein preferably the olefin is one or more of ethylene, propylene, 1-butene, 2-butene, and isobutylene, the alkane is one or more of alkanes containing 2 to 18 carbon atoms, and the aromatic compound is one or more of benzene, toluene and xylene.

15. A fluidized bed or fixed bed reactor for converting oxygenates to hydrocarbons, the reactor comprising a catalyst for converting oxygenates to hydrocarbons and an adsorbent material capable of adsorbing water, wherein the catalyst and the adsorbent material are different.

Citation Information

Patent Citations

  • Process for Converting Oxygenates to Olefins

    US20150119617A1

  • Zeolitic 3D scaffolds with tailored surface topography for methanol conversion with light olefins selectivity

    US20190001311A1

  • Process for converting oxygenates to olefins with direct product quenching for heat recovery

    WO1999055650A1

  • Stabilizing catalyst activity during catalyst regeneration

    WO2006104757A2